Marshall and stickler syndrome in one family - Tomčíková, D; Bušányová, B; Krásnik, V; Gerinec, A (Ceska a slovenska oftalmologie, 2018)
The authors present the ocular finding in a patient sent to the Department of Paediatric Ophthalmology at the Children's University Hospital - Faculty of Medicine, Comenius University in Bratislava at the age of 3 months, with congenital glaucoma in her right eye and bilateral high myopia. The family anamnesis of the patient shows repeated occurrence of stunted growth, myopia, facial dysmorphia and cataract. The child's mother had high myopia, the mother's brother underwent cataract surgery, the child's grandmother and her sisters and the child's great grandmother had high myopia and glaucoma, and probably underwent cataract surgery at a young age. The child's mother and grandmother underwent a genetic examination, with a conclusion of Marshall syndrome. Within the framework of neonatal screening, poor cortical auditory evoked potential, a defect of the interventricular septum and bifid uvula were diagnosed in the child. With regard to the overall finding in the patient and the genetic family history, we suspected Marshall syndrome. A genetic examination determined Stickler syndrome type 1 with the presence of mutation in the COL2A gene (variant c.2710C >T (p.Arg904Cys,rs121912882)). Due to high intraocular pressure with the impossibility of compensation by medication, bilateral trabuculectomy was performed on the patient. At present the patient has intraocular pressure compensated with adjuvant medicamentous therapy. With regard to high myopia and pronounced degenerative changes on the periphery of the retina in the sense of lattice degeneration, preventive cryopexy of the retinal periphery is planned. A molecular genetic analysis helped diagnose the pathology as Stickler syndrome type 1, which manifested phenotype symptoms of Marshall syndrome or Stickler syndrome type 2. Key words: Marshall syndrome, Stickler syndrome, mid-facial dysmorfism, myopia, glaucoma, cataract.
Keywords: Retinal Detachment; Connective Tissue Diseases; Infant; Humans; kojenec; myopie; Marshall syndrome; Female; Myopia; odchlípení sítnice; Hearing Loss, Sensorineural; glaucoma; lidé; Arthritis; cataract; myopia; Pedigree; rodokmen; ženské pohlaví; mid-facial dysmorfism; Male; artritida; nemoci pojiva; Stickler syndrome; mužské pohlaví; percepční nedoslýchavost